Authentication of lemon grass (Cymbopogon citratus) essential oil using fourier transform infrered-atenuated total reflectance spectroscopy in conjuction with principal component analysis - Tomulto, Ma. Teresa Mamarion (2016.)
Lemongrass essential oil is considered as one of the most important essential oil in the whole world. It is widely known for its antimicrobial activities and for its aromatic and flavouring contents. In addition, lemongrass essential oil has a strong marketing advantage which makes its price higher than synthetic ones and may result to many cases of adulteration. This study was designed for authentication of lemongrass essential oils using FTIR-ATR spectroscopy in conjunction with Principal Component Analysis (PCA). The commercially obtained lemongrass essential oils were authenticated by the comparison of their IR spectra to distilled lemongrass essential oils and other commercially obtained limonene-containing essential oils. It was observed that the lemongrass essential oils from its different parts and different locations often differ in their OH peak, aldehyde C=O peak and the fingerprint region. These differences may be due of the dissimilarities in their percentage composition of nerol, geraniol, linalool, borneol, neral and geranial. All the spectra were then further reduced through the PCA for a clearer visualization. The different essential oils were found to be grouped in PCA scores plot accordingly and as expected. Thus, FTIR-ATR spectroscopy in conjunction with PCA can indeed authenticate lemongrass essential oils.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Lemon grass (Cymbopogon citratus); Essential Oil -- Lemongrass